1980
DOI: 10.1182/blood.v56.6.947.bloodjournal566947
|View full text |Cite
|
Sign up to set email alerts
|

The nature and action of granulocyte-macrophage colony stimulating factors

Abstract: Granulocyte-macrophage colony stimulating factor (GM-CSF) stimulates the in vitro proliferation and differentiation of granulocytic and macrophage cells. This regulator is now known to act at other levels of hemopoietic regulation. The heterogeneity of GM-CSFs is not only related to the tissue of origin and the in vitro production method, but also to functional subclasses of the molecule that have distinct biologic specificities. Most adult mouse organs produce GM-CSF (mol wt 23,000), but a macrophage (M)-CSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
1

Year Published

1983
1983
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 0 publications
0
63
1
Order By: Relevance
“…with LPS (SO pg) and AE (300 pg) followed by in vitro stimulation with Con A (5 pgiml) for 24 h. Con A-activated T91-4 and Tll-14 hybridoma supernatants were prepared as rat Con A supernatants (see above), but without further purification. They contained no detectable quantities of T cell growth factor (IL2) [47] or CSF [48] but had BRF and BMF activity [25]. Conditioned media were used in the presence of 5 mM a-methylmannoside (Sigma Chemical Co., St. Louis, MO).…”
Section: Factors From T Cell Hybridomasmentioning
confidence: 99%
“…with LPS (SO pg) and AE (300 pg) followed by in vitro stimulation with Con A (5 pgiml) for 24 h. Con A-activated T91-4 and Tll-14 hybridoma supernatants were prepared as rat Con A supernatants (see above), but without further purification. They contained no detectable quantities of T cell growth factor (IL2) [47] or CSF [48] but had BRF and BMF activity [25]. Conditioned media were used in the presence of 5 mM a-methylmannoside (Sigma Chemical Co., St. Louis, MO).…”
Section: Factors From T Cell Hybridomasmentioning
confidence: 99%
“…By clonal assay of bone marrow cells using the semi-solid culture system, it has been shown that neutrophilic granulocytes originate from multipotent stem cells and that the proliferation and differentiation in vitro of the progenitor cells of the granulocytemacrophage lineage are regulated by a family of glycoproteins (Sachs, 1970;Metcalf, 1977;Burgess and Metcalf, 1980). These molecules are generally called colonystimulating factors (CSFs) or macrophage and granulocyte inducers (MGIs) (Landau and Sachs, 1971;Sachs, 1978Sachs, , 1980; on the basis of morphology of the colonies stimulated, these factors are classified into at least four biochemically distinct subtypes, that is, multi-, granulocyte-macrophage (GM)-, macrophage (M)-and granulocyte (G)-CSFs (Metcalf, 1985;Sachs, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation and differentiation of the progenitor cells for granulocytes and macrophages are regulated by a family of proteins called colony-stimulating factors (CSF) (Burgess and Metcalf, 1980;Metcalf, 1985). In the murine system, four CSFs have been well characterized; granulocyte-macrophage CSF (GM-CSF), granulocyte CSF (G-CSF), macrophage CSF (M-CSF) and interleukin 3 (IL-3) (Metcalf, 1985).…”
Section: Introductionmentioning
confidence: 99%